2020
DOI: 10.3389/fmats.2020.00221
|View full text |Cite
|
Sign up to set email alerts
|

Probing on the Stable Structure of Silicon-Doped Charged Magnesium Nanomaterial Sensor: SiMgn±1 (N = 2−12) Clusters DFT Study

Abstract: The stable structures of silicon-doped charged magnesium nanomaterial sensor, SiMg n ±1 (n = 2−12) clusters, were systematically investigated using the CALYPSO approach coupled with the density functional theory (DFT). The growth mechanism of SiMg n ±1 (n = 2−12) nanosensors shows that the tetrahedral and tower-like structures are two basic structures, and almost all other clusters' geometries are based on their variants. Most importantly, the fascinating SiMg 8 −1 and SiMg 8 +1 clusters are obtained through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In this work, further detailed research was performed for the most stable cluster, including ultraviolet-visible absorption spectrum (UV-Vis), infrared (IR) and Raman spectra, hole-electron [40] and natural transition orbitals (NTO) [41] analysis of its electronic excitation characteristics. In addition, Multiwfn [42] and VMD [43] software were also used to analyze and plot some properties related to the wave function properties of clusters.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, further detailed research was performed for the most stable cluster, including ultraviolet-visible absorption spectrum (UV-Vis), infrared (IR) and Raman spectra, hole-electron [40] and natural transition orbitals (NTO) [41] analysis of its electronic excitation characteristics. In addition, Multiwfn [42] and VMD [43] software were also used to analyze and plot some properties related to the wave function properties of clusters.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, research found that heteroatom doping is an effective strategy to stabilize geometrical structures or to tune electronic properties. Up to now, based on the different quantum chemistry calculations, studies on metal-doped (Be, Al, Ge, Sn, 3 d and 4 d TM atoms) and nonmetal-doped (B, C, N, O, F and Si) magnesium clusters have harvested many great achievements [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. More importantly, based on the CALYPSO structural searching method and DFT, the structures and electronic properties of Be-, Be 2 -, Sr 2 - and Ba 2 -atom-doped differently sized magnesium clusters have been systemically discussed by Zeng’s, Zhao’s and our groups [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%